The history of live music in Britain. from Live Aid to Live Nation /: from Live Aid to Live Nation. 1985-2015 : Volume III, (2021) - Frith, Simon, 1946-; Brennan, Matt; Cloonan, Martin; Webster, Emma
No abstract available